PEMANFAATAN LITERASI DIGITAL TERHADAP PESAN DAKWAH KH. SALAHUDDIN WAHID PADA MEDIA TEBUIRENG ONLINE - Setyawan Saputro, Dimas; Mus Qoimah , Al Hidayahtul; Nurdin, Ali (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2024)
Today's da'wah cannot always rely on old methods in conveying it to the wider community. The use of da'wah media, in the form of digital literacy, is one of the inevitability that must be taken by every da'i, preacher, ustadz to a kyai, if they want their da'wah to be accepted by the community that is eroded by the demands of the times. The purpose of compiling this scientific paper is to try to describe how KH. Salahuddin Wahid broadcasts his da'wah through digital literacy which in this case focuses on analyzing the Tebuireng Online website. In his research, the researcher found that KH. Salahuddin Wahid's da'wah media through digital literacy was able to reach the wider community. Although Tebuireng Online seems like a pesantren media only, the researcher found some interesting content displayed on the media, such as podcast content on the Youtube channel, educational content on Instagram, then writings about religious treatises with an Islamic nuance Rahmatan Lil A'lammin, This study uses a qualitative descriptive method. The qualitative descriptive approach is a research approach where the data collected are in the form of words, pictures and not numbers. The data can be obtained from interviews, field notes, photos, video tapes, personal documentation, notes, or memos and other documentation.